Performance Training for the Development of the Harmonic Ability and its Impact on the Rapid Force and the Achievement of (50) Meters of Breast for Junior - Wadad Kadhim Majid (Journal of Global Pharma Technology, 2019)
In the introduction and importance of the research, the importance of the muscular ability to harmonize the formation and formulation of specific physical characteristics of many games with motor performance, including swimming, which need to link the strength and speed together to the muscles working in the performance, and the importance of research in the use of training exercises to perform muscle training Harmonic characteristic of the speed of the muscles of the arms and legs to promote the players, which in turn is working on the development of the completion of (50) meters breast. The problem of research is that many players are characterized by good physical and physical ability, but cannot perform any movements that require a certain amount of coherence and compatibility at the same time, the chest swell is far from the normal movements performed by the player in his public life, as well as it needs to High level of motor timing and muscle compatibility, which is the blows of the legs and the blows of the arms and the process of linking them to the breathing process, which are not familiar to the swimmer, especially in the younger ages of them. The aim of the study is to prepare a performance training to develop the musculoskeletal capacity of the two legs and arms of the young swimmers. 2 - Identify the effect of special exercises in the development of the rapid strength of the muscles of the legs and arms and the completion of the 50-meter breaststroke ages (11-13) years. The research hypothesis is that there are statistically significant differences in the effect of adaptive ability exercises in the results of the pretests on the dimension in the development of the rapid strength of the muscles of the legs and arms and the completion of (50) m. The researchers identified the research society and its sample with the specialized school for boys (11-13 years old) and officially registered in the Central Swimming Federation who continue in training and competition in the sports season (2017-2018) of (8) swimmers. Their number (4) players. Four of them were excluded due to repeated absence, thus representing 50% of the research community. The special exercises were carried out within the training curriculum for the sample which lasted eight weeks and three days a week for 24 training units. The researchers found several conclusions that the special compatibility ability exercises led to the development of muscular strength of the arms and legs in the junior swimming pool. Special compatibility resulted in the development of muscular capacity for both arms and legs, which had a good effect in the development of the digital achievement of (50) meters in the sample junior swim.Keywords: Performance training, harmonic ability and rapid force.